Accelerating organisation culture change : innovation through digital tools - Lee, Jaclyn (Emerald points., 2020)
This book introduces an innovative new digital approach to speed up cultural change in organisations and reduce failure rates through use of the Culture Acceleration Tool and Methodology (CATM). This tool combines the methodology of the Organizational Cultural Assessment Instrument (OCAI), Action Design Thinking and Group Decision Support Systems. In order to transform employee mindsets and align workforces to the strategic goals of their organisation in Industry 4.0, culture change and organisational transformation is necessary. However, culture change is a complex process which takes years to complete, often with low success rates. In Accelerating Organisation Culture Change, Jaclyn Lee presents resolutions to these issues through the CATM toolkit that combines capabilities of diagnosing culture, refining the change process, and using a digital platform to brainstorm and set clear goals for change management. Including real life case studies on the application of CATM in organisations, the book demonstrates the possibility of a higher success rate with organisational culture change management, and provides researchers, organisations and practitioners with a clear roadmap on how to develop the CATM toolkit for their own culture transformation journey.